Effect of patent ductus arteriosus on the heart in preterm infants. (27th February 2019) - Philip, Ranjit; Towbin, Jeffrey A.; Sathanandam, Shyam; Goldberg, Jason; Yohannan, Thomas; Swaminathan, Nithya; Johnson, Jason Nathaniel
Abstract: There continues to be controversy on the long‐term effects of a patent ductus arteriosus (PDA) and its management. However, the hemodynamic effects of a large PDA in a preterm infant are well known. This article aims to provide insight into the adaptive changes and remodeling effects of a PDA on the myocardium in preterm infants.